DEVELOPMENT OF ADOBE FLASH CS6-BASED LEARNING MEDIA ON ARTHROPODE MATERIALS - Putri Pratiwi; Elida Hafni Siregar (Universitas Negeri Medan, 2021)
This study aims to develop learning media based on Adobe Flash CS6 on Arthropod material and produce appropriate learning media based on the assessments of material experts, media experts, and students. This research applies a 4-D development model using. Each learning media validator consists of two material experts and two media experts. The small group trial subjects were 26 biology students, while the significant group trial subjects were 78 biology education students. The research data was obtained from a questionnaire on the feasibility of learning media from material experts, media experts, and student response questionnaires. The data obtained were analyzed by descriptive analysis techniques. The results showed that the validation of material experts and media experts obtained an average value of 97.5 and 102.5, respectively, in the very feasible category. The small group trial and large group trial results obtained an average value of 93 and 104.1, respectively, in the very feasible category. The resulting learning media is declared valid and very suitable to be used as a learning medium for biology students at the State University of Medan on Arthropoda material.